Who requires dental treatment under general anesthesia due to pain and severe dental anxiety? Findings from panoramic X-ray images and anamnesis - Vilde Aardal; Caroline Hol; Anne Rønneberg; Sudan Prasad Neupane; Tiril Willumsen (Acta Odontologica Scandinavica)
Objective: The aims were to describe the dental status and mental and somatic health profile of patients with severe dental anxiety requiring dental treatment under general anesthesia (GA) in Rogaland County, Norway (2018–2021), and to compare patients with and without reported abuse history.